DEVELOPMENT OF LEARNING MEDIA PICTURE BOOKS BASED ON LOCAL WISDOM KUDUS INDONESIAN LANGUAGE SUBJECTS POETRY WRITING MATERIAL FOR GRADE V STUDENTS OF PRIMARY SCHOOLS - Slamet, Mohammad (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2019)
This research was conducted to describe the analysis of the needs of students and teachers towards the development of picture book learning media based on sacred local wisdom in grade V elementary school students. Making prototypes of learning media picture books on Indonesian subjects poetry writing material for fifth grade elementary school students. the use of learning media Indonesian picture books subject matter poetry writing for elementary school students in grade V.Using research and development methods, or also called Research and Development. Research and Development method (RnD) is a research method used to produce certain products, and test the effectiveness of these products. The research was conducted at SD 4 Peganjaran, SD 4 Gribig, SD 1 Gribig and SD NU Kartika in Kudus City. The research subjects were all teachers, fifth grade students from four different schools namely 3 Peganjaran Public Elementary School in Bae sub-district, 4 Gribig Public Elementary School in Gebog sub-district, 1 Gribig Public Elementary School in Gebog sub-district and Nawa Kartika elementary school in Kota sub-district.The test results of the effectiveness of picture book learning media are based on holy local wisdom in Indonesian language. Testing effectiveness is done by comparing the results of each school's pretest and posttest. Based on the value of t test at SD 3 Peganjaran obtained So the acquisition of t count = 4, 542 while T table = 1.79, t test can be concluded t count> t table So Ho is rejected and Ha is accepted, so Ha is accepted and media of effective picture book applied. Based on the test value at SD 4 Gribig obtained t count = 4.73 while T table = 1.73 t test can be concluded t count> t table Then Ho is rejected and Ha is accepted so that Ha is accepted and media picture book is effectively applied. Based on the t test on SD 1 Gribig obtained t value = 6.98 while T table = 1.68 t test can be concluded t count> t table Then Ho is rejected and Ha is accepted, so that Ha is accepted and media picture book is effectively applied, Based on the value Nawa Kartika's NU SD test obtained t count = 8.07 while T table = 1.68 t test can be concluded t count> t table So Ho is rejected and Ha is accepted, so Ha is accepted and media picture book is effectively applied.